The Bengali Language Movement and Emergence of Bangladesh - Islam, Rafiqul (Dhaka University Journal of Linguistics, 2009)
This paper offers a brief history of the Bengali language movement in Pakistan from 1948 to 1952 and depicts the events how Bengali was incorporated as one of the state languages of Pakistan in its constitution in 1956. It also describes how that constitution was scrapped by the Military rulers of Pakistan in 1958 and marked Bengali as one of the national languages of Pakistan in 1963 constitution promulgated by the military janta. So, Bengali language, the language of the majority citizens of Pakistan had to wait to be a state language till the establishment of the independent Bangladesh through prolonged political agitation and a bloody war of liberation in 1971. Ultimately, Bengali was made the state language of the Peoples Republic of Bangladesh in its constitution of 1972. Dhaka University Journal of Linguistics Vol.1(1) 2008, 221-232